2015
DOI: 10.1039/c5ta01853f
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure formation mechanism and ion diffusion in iron–titanium composite materials with chemical looping redox reactions

Abstract: Fe–Ti microparticles and their oxidation and redox processes in chemical looping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…On the stoichiometric surface, CH adsorption on Fe atop site is the most favorable configuration (CH@S-A). 34 Therefore, we can control the oxygen vacancy concentration of oxygen carriers to increase the activity of oxygen carriers by adding suitable support materials, which will be our future work. In contrast, the most favorable configurations for CH on the defective surface with oxygen vacancies are CH@Vo(1)-A and CH@Vo(1)-D. Thus, we consider two possible reaction pathways for the dissociation of CH on the defective surface: (1) (1) and (2) pathways are 146.33 kJ mol À1 and 142.8 kJ mol À1 (T d 4), respectively.…”
Section: Ch 4 Dissociation On Defective A-fe 2 O 3 Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the stoichiometric surface, CH adsorption on Fe atop site is the most favorable configuration (CH@S-A). 34 Therefore, we can control the oxygen vacancy concentration of oxygen carriers to increase the activity of oxygen carriers by adding suitable support materials, which will be our future work. In contrast, the most favorable configurations for CH on the defective surface with oxygen vacancies are CH@Vo(1)-A and CH@Vo(1)-D. Thus, we consider two possible reaction pathways for the dissociation of CH on the defective surface: (1) (1) and (2) pathways are 146.33 kJ mol À1 and 142.8 kJ mol À1 (T d 4), respectively.…”
Section: Ch 4 Dissociation On Defective A-fe 2 O 3 Surfacesmentioning
confidence: 99%
“…32 There have been a few DFT studies on the defect properties of Fe 2 O 3 . 34 Wanaguru et al 35 modeled hematite nanoribbons, and showed that built-in oxygen vacancies can be produced on the edge. 34 Wanaguru et al 35 modeled hematite nanoribbons, and showed that built-in oxygen vacancies can be produced on the edge.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction kinetics of Fe 2 O 3 /Al 2 O 3 and Fe 2 O 3 /Al 2 O 3 /TiO 2 with methane are regressed and calculated by the shrinking core model (SCM), as described in eqn (6)- (11). Aer tting the conversion curves, the kinetic parameters are summarized in Table 2.…”
Section: View Article Onlinementioning
confidence: 99%
“…Also, the preparation methods are usually employed, tuning the nanostructure of the material in attempt to better chemical looping performance . The iron‐titanium based oxides are tested by Fan's group and the results revealed that the iron‐titanium based oxides used as enabling materials in energy conversion systems can greatly improve the reactivity of iron oxides alone over multiple redox cycles in chemical looping applications and the drastically improved performance for iron based oxygen carrier particles after support addition appears to result from the enhanced oxygen anion diffusivity rather than increased initial porosity and sintering resistance . Our current work is also to tune these sintering related parameters aiming at producing stable OC materials, but herein we just focus on the material porosity.…”
Section: Introductionmentioning
confidence: 99%